Analisis Strategi Penerjemahan Metafora pada Lagu “Skyfall” oleh Adele - Gessyela Putri; Misyi Gusthini (LPPM Universitas Terbuka, 2022)
This study employs a method of metaphor translation from English to Indonesian to assist music listeners in comprehending the lyrics of Adele’s song “Skyfall.” The author’s problem in doing the analysis is sources text with metaphorical interpretation cannot be translated using literal translation; instead, a metaphor translation strategy is required. In order to analyze the text, the author employed a descriptive qualitative research method. By gathering and logging data, nine data were discovered from this research. This study uses a song written and performed by Adele, who also the theme song for the movie with the same title. The study's findings indicate that, of the nine metaphors found in the song